2005
DOI: 10.1002/ajh.20294
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine causes severe vacuolar myopathy in a patient with chronic graft‐versus‐host disease

Abstract: A 51-year-old man developed progressive debilitating limb and respiratory muscle weakness while undergoing treatment for chronic graft-versus-host disease secondary to allogeneic bone marrow transplant for mantle cell lymphoma. He had a normal serum creatine kinase level and acetylcholine receptor antibodies were negative. Electromyography showed a severe, nonirritable myopathy and a sensory motor axonal polyneuropathy. A muscle biopsy showed a necrotizing, vacuolar myopathy with many fibers containing autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
(25 reference statements)
0
18
0
2
Order By: Relevance
“…However, recent studies provided compelling evidence that autophagy protected against neurodegenerative diseases and the accumulation of autophagosomes primarily represented the activation of beneficial physiological process [15,16]. Danon disease, which is a kind of genetic myodegenerative disease, was characterized by the extensive accumulation of autophagosomes [17]. As a result, a general point of view seems to emerge that the autophagy pathway apparently improves survival via clearance of aggregate-prone proteins [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies provided compelling evidence that autophagy protected against neurodegenerative diseases and the accumulation of autophagosomes primarily represented the activation of beneficial physiological process [15,16]. Danon disease, which is a kind of genetic myodegenerative disease, was characterized by the extensive accumulation of autophagosomes [17]. As a result, a general point of view seems to emerge that the autophagy pathway apparently improves survival via clearance of aggregate-prone proteins [18].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The development of this side-effect does not appear to be dose-dependent. 4 No report of myopathy from the quinines has been reported before 6 months of continued intake.…”
Section: Sirmentioning
confidence: 94%
“… Pre-existing myopathy and/or neuropathy, due to the potential risk of HCQ-induced neuromyotoxicity. (58)(59)(60)(61)(62)(63)  Glucose-6-phosphate dehydrogenase (G6PD) deficiency, due to the potential increased risk of HCQ-related hemolysis crisis. (64) Interestingly, Heymann et al (65) found a significantly higher proportion of G6PD-deficient patients among the diabetic population aged 45-64 years.…”
Section: Accepted Articlementioning
confidence: 99%